Analysis and design of marine structures [electronic resource] - International Conference on Marine Structures (2009 : Lisbon, Portugal); Soares, C. Guedes; Das, P. K. (Purnendu K.) (Boca Raton, FL : CRC Press, 2009)
Includes bibliographical references and index